PENGARUH KARAKTERISTIK EKSEKUTIF TERHADAP MANAJEMEN LABA - Widya Rovita Dewi; Theresia Woro Damayanti (Jurnal Akuntansi Profesi, 2020)
Earnings management is an activity of earnings information manipulation carried out by company management in accordance with management's wishes to maximize or minimize profit in financial statements. There are many factors that influence earnings management carried out by the company, one of which is executive characteristics. The purpose of this study was to examine the effect of executive characteristics, namely CEO and CFO on earnings management. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2015 - 2018 which were obtained using a purposive sampling method. Data analysis used descriptive statistics, stationarity test, and panel data regression analysis. The results showed that CEO and CFO age, CEO tenure, and CEO education level had a positive effect on earnings management and CFO tenure had a negative effect on earnings management. Keywords: Earnings Management, Executive, Age, Gender, Education Level, Tenure, Bonus Compensation.